Influência de agentes clareadores na resistência de união de um sistema restaurador ao esmalte em função do tempo de armazenamento em saliva artificial - Borges, Alessandra Buhler [UNESP] (2003)
The aim of this study was to determine the effect of three bleaching agents on the shear bond strength of a composite resin to enamel, after various artificial saliva storage time (1 day, 1, 2 and 3 weeks). 78 human premolars were mesiodistally sectioned to obtain two halves. The buccal and lingual surfaces were ground with 600-grit aluminum oxide abrasiva paper to obtain flat enamel surfaces and divided into a control group (n=12) and three experimental groups (n=48), according to the bleaching agents. The first group was bleached with Crest Professional Whitestrips (6,5% hydrogen peroxide), used 1 hour for 14 days. The second group was bleached with Opalescence Quick (35% carbamide peroxide), in three applications of 1h, with an interval of 7 days among them. The third group was bleached with Opalescence Xtra (35% hydrogen peroxide), in three applications of 16min, with an interval of 7 days among them. Specimens of control group were not bleached and were stored in artificial saliva at 37ºC for 14 days. After the bleaching treatments, the specimens of the experimental groups were divided into four groups (n=12), according to the storage time in artificial saliva (1 day, 1, 2 and 3 weeks). Bonds were formed with Scotchbond MP and Z-100 composite resin, and shear bond test was carried out in an lnstron Universal Testing Machine after 24 hours. The results were analyzed by two-way ANOVA, Tukey and Dunnett's tests (5%). There was no significant difference among the shear bond strength of the three bleaching agents. Regarding to the post-bleaching time, the bond strength values obtained after three weeks were significant higher than the values obtained after one day, one and two weeks and were similar to those obtained for the control group. Conclusion: external bleaching with the three agents tested significantly reduced the bond strength of composite resin to enamel and after a lapse of ...